2011
DOI: 10.1089/adt.2010.0288
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cell-Based, High-Throughput Screening Assay for Cholesterol Efflux Using a Fluorescent Mimic of Cholesterol

Abstract: Reverse cholesterol transport is the process by which extrahepatic cells, including macrophage-derived foam cells in arterial atherosclerotic plaque, transport excessive cholesterol back to the liver for bile acid synthesis and excretion, thus lowering the peripheral lipid burden. Cholesterol efflux from peripheral cells is the first step in this process, and finding drugs and interventions that promote this event is an important endeavor. Radioisotope-labeled cholesterol traditionally has been employed in mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…This assay uses the Pennsylvania Green fl uorophore attached by a linker containing a glutamic acid residue to a derivative of N-alkyl-3 ␤ -cholesterylamine ( 32 ). The fractional release of this compound is less than that obtained with [use of the BODIPY-cholesterol effl ux assay, as described in this study, has the potential of streamlining studies linking cell cholesterol effl ux to clinical endpoints such as IMT and angiography.…”
Section: Discussionmentioning
confidence: 97%
“…This assay uses the Pennsylvania Green fl uorophore attached by a linker containing a glutamic acid residue to a derivative of N-alkyl-3 ␤ -cholesterylamine ( 32 ). The fractional release of this compound is less than that obtained with [use of the BODIPY-cholesterol effl ux assay, as described in this study, has the potential of streamlining studies linking cell cholesterol effl ux to clinical endpoints such as IMT and angiography.…”
Section: Discussionmentioning
confidence: 97%
“…These fluorescent cholesterol analogs have also demonstrated significant potential as substitutes for traditional radioisotope-labeled cholesterol for investigating lipid trafficking, including cholesterol efflux (7,22). Cholesterol efflux may prevent the development of atherosclerosis by reducing the accumulation of cholesterol in the artery wall (2,23) and is a key step in RCT.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Zhang et al developed fluorescent cholesterol bearing the Pennsylvania Green fluorophore for use as a molecular probe for the cholesterol efflux assay. This fluorescent sterol exhibits good correlation with radioisotope-labeled cholesterol in the efflux assay in THP-1 cells (24). Sankaranarayanan et al demonstrated that another fluorescent sterol, bearing a BODIPY fluorophore, can be used as a sensitive probe in the cholesterol efflux assay in J774 mouse macrophages (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations